The multidimensional study of the elderly in the family health strategy in Porto Alegre, Brazil (EMI-SUS) - Gomes, Irenio; Nogueira, Eduardo Lopes; Engroff, Paula; Ely, Luísa Scheer; Schwanke, Carla Helena Augustin; Carli, Geraldo Attilio De; Resende, Thais de Lima (PAJAR - Pan-American Journal of Aging Research, 2013)
Population aging is a global phenomenon never experienced before, which will cause major repercussions for the health area. This paper’s main objective is to describe the methods employed in a transversal epidemiological study with a target sample of 1080 elderly people, randomly selected from the Family Health Strategy in Porto Alegre (RS/Brazil). It integrates three key dimensions: epidemiological, clinical and basic sciences. A sub-sample with changes in cognition or mood make up a longitudinal study. The relevance of this work rests primarily on the synergy between research and care; aiming to improve health care for the elderly and making better use of the Brazilian National Health Service structure. In this way, there is a combination of robust methodological tools capable of accurately observing the epidemiological phenomena, associated with research in the areas of basic and multidisciplinary sciences. Research initiatives like this can bring forth benefits to a large proportion of the population who depend on the public health structure.